Effect of low and high frequency electro-acupuncture stimulation on heart rate variability and behavioural indicators in horses - Van Vollenhoven, Elize (University of Pretoria, 2022)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2020.